The Impact of Fear of Missing Out on Self-Confidence Among Generation Z in the Social Media Era - Santoso, Arysatya Syandana Ararya; I Wayan Radityakara Wirasena Yassa; Dyah Arista Putri; Nur Aulia Ahya Ningsih (Jurnal Biologi Tropis, 2025)
Generation Z in Indonesia, as a active users of social media with an average usage of more than three hours per day, faces psychological challenges due to the phenomenon of Fear of Missing Out (FoMO). This literature review aims to analyze the relationship between FoMO and self-confidence among Gen Z in the context of social media through a descriptive-qualitative approach by integrating recent literature (2015-2025) from reliable databases. The findings show that FoMO triggered by social media platform, hustle culture, and social comparison significantly reduces self-confidence through mechanisms of self-comparison with unrealistic life standards in the digital word. Approximately 64.6% of Indonesian adolescents experience FoMO, which is associated with social anxiety, decreased self-esteem, and distorted self-perception. The impact is exacerbated by social media algorithms that selectively present idealized content, reinforcing cycles of dependency and psychological fatigue. This study identifies the need multidimensional approaches including digital literacy education, school- based mental health interventions, and platform regulations to reduce exposure to social comparison-triggering content. The findings emphasize the urgency of collaboration among governments, educational institutions, and platform providers in fostering Gen Z’s critical awareness regarding healthy social media use.